Collecting High-Frequency Data Using Mobile Phones : Do Timely Data Lead to Accountability? - Croke, Kevin (World Bank, Washington, DC, 2014)
As mobile phone ownership rates have risen dramatically in Africa, there has been increased interest in using mobile telephones as a data collection platform. This note draws on two largely successful pilot projects in Tanzania and South Sudan that used mobile phones for high-frequency data collection. Data were collected on a wide range of topics and in a manner that was cost-effective, flexible, and rapid. Once households were included in the survey, they tended to stick with it: respondent fatigue has not been a major issue. While attrition and nonresponse have been challenges in the Tanzania survey, these were due to design flaws in that particular survey, challenges that can be avoided in future similar projects. Ensuring use of the data to demand better service delivery and policy decisions turned out to be as challenging as collecting the high-quality data. Experiences in Tanzania suggest that good data can be translated into public accountability, but also demonstrate that just putting data out in the public domain is not enough. This note discusses lessons learned and offers suggestions for future applications of mobile phone surveys in developing countries, such as those planned for the World Bank's "Listening to Africa" initiative.